Deformity Reconstruction Surgery for Tibial Hemimelia - David Y. Chong; Dror Paley (MDPI AG, 2021)
Tibial hemimelia is a rare congenital deficiency with a wide spectrum of pathology and deformity. This paper aims to give a comprehensive review of tibial hemimelia, with a concise summary of the history, pathology, and clinical findings of tibial hemimelia, while providing treatment recommendations and a review of the current literature. Classifications and surgical treatments are discussed, including amputation, limb reconstruction, and lengthening. Type-specific treatments are also discussed, including staged distraction correction of joint contractures of knee and ankle, Weber patelloplasty, fibular centralization, knee and ankle arthrodesis, implantable articulated distractors, and the role of femoral shortening. Amputation is a simpler and easier solution for many patients; however, reconstruction options continue to evolve, improve, and provide better functional outcomes in many cases. Factors favoring surgical reconstruction include the presence of a knee joint/proximal tibia, and the presence of a patella and quadriceps mechanism.